2023
DOI: 10.1097/aci.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

COPD and biologic treatment: state of the art

Abstract: Purpose of review Chronic Obstructive Pulmonary Disease (COPD) is a common, heterogeneous disease associated with abnormal inflammatory response of the lung to noxious particles and gases. The progression of disease leads to respiratory failure, disability and premature death. Although recent progress in reducing the global burden of many chronic disease, such as heart disease and cancer, mortality and morbidity due to COPD continue to increase despite of cigarette smoking worldwide policy. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Some studies have suggested that smoking is the main environmental factor triggering COPD, but other factors also include airway hyperresponsiveness, sex, genetics, occupation, lung growth, and development[ 101 , 102 ]. Currently available treatment methods for COPD, which mainly focus on treating the symptoms and slowing the progression of these disorders, include anti-inflammatory drugs, corticosteroids, long-acting muscarinic antagonists, and β2-adrenergic receptor agonists[ 103 , 104 ]. These treatments may help minimize airflow limitation and future exacerbations but cannot reverse lung damage or improve quality of life in patients with COPD.…”
Section: Current Research Advancements In the Use Of Uc-mscs For Pulm...mentioning
confidence: 99%
“…Some studies have suggested that smoking is the main environmental factor triggering COPD, but other factors also include airway hyperresponsiveness, sex, genetics, occupation, lung growth, and development[ 101 , 102 ]. Currently available treatment methods for COPD, which mainly focus on treating the symptoms and slowing the progression of these disorders, include anti-inflammatory drugs, corticosteroids, long-acting muscarinic antagonists, and β2-adrenergic receptor agonists[ 103 , 104 ]. These treatments may help minimize airflow limitation and future exacerbations but cannot reverse lung damage or improve quality of life in patients with COPD.…”
Section: Current Research Advancements In the Use Of Uc-mscs For Pulm...mentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is an incurable chronic respiratory disease, characterized by persistent respiratory symptoms and airflow restriction due to airway or alveolar abnormalities. 1 The morbidity and mortality of COPD are rising every year worldwide and the World Health Organization estimates that COPD will be the third leading cause of death in the world by 2030. 2 Although our understanding of COPD is improving, the pathological mechanism of COPD has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%